A New Science for Future Climate Impact Modeling and the Quest for Digital Openness - Hirsbrunner, Simon David (Locating Media/Situierte Medien, 2021)
Building on concepts from Science & Technology Studies, Simon David Hirsbrunner investigates practices and infrastructures of computer modeling and science communication in climate impact research. The book characterizes how scientists calculate future climate risks in computer models and scenarios, but also how they circulate their insights and make them accessible and comprehensible to others. By discussing elements such as infrastructures, visualizations, models, software and data, the chapters show how computational modeling practices are currently changing in light of digital transformations and expectations for an open science. A number of inventive research devices are proposed to capture both the fluidity and viscosity of contemporary digital technology.